Needs of Libraries with Rich Islamic Collections: Classification Dilemma and Optimal Solution for Islamic Knowledge - Idrees, Haroon (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Standard library classification systems (e.g., DDC, LCC, UDC) are convenient information organization tools. Libraries with rich collections on Islam face problems; hence, use expansions/indigenous systems. This poster examines this problem and presents a potential optimal solution, based on data from 30 libraries and 16 LIS Scholars from nine countries. Les systèmes de classification documentaires standards (p. ex. DDC, LCC, UDC) sont des outils d’organisation de l’information pratiques. Les bibliothèques avec de riches collections sur l’Islam font face à des problèmes et elles doivent utiliser des systèmes complémentaires ou ad hoc. Cette affiche examine ce problème et présente une solution optimale potentielle, basée sur les données de 30 bibliothèques et 16 chercheurs en BSI de neuf pays.